The daily life of migrant workers in Tuvan and Molotov forestry in the 1940s and 1950s - Kimerling, Anna S.; Shabalin, Vladislav V. (The New Research of Tuva, 2025)
This article reconstructs and compares the everyday experiences of forestry workers in the Tuvan Autonomous Oblast and Molotov Oblast during the 1940s–1950s. The study is based on materials collected from state archives of the respective territories. The theoretical and methodological framework employed is the theory of everyday life as interpreted by M. de Certeau, who describes people’s modes of action through the concepts of power strategies and responsive tactics. D. North’s theory of institutional traps provides an explanatory model for the significance of informal tactics in solving formal tasks.In both regions, the management system of forestry enterprises was established in the postwar period. Practically all forestry employees can be classified as various categories of migrants. Workers in timber enterprises were recruited via diverse methods — organizational recruitment predominated in Tuva, rural residents were persuaded to transfer from collective farms to forestry jobs, and managerial staff were recruited from other regions of the USSR. Most Molotov workers were mobilized through labor deployment or arrived in the Urals as a result of forced displacement. Forestry enterprises in both oblasts suffered from high employee turnover and a persistent shortage of labor force, attributable in part to the challenges encountered by workers in their daily lives.Problems were largely similar in both regions: housing provision was inadequate, many newly arrived logging workers resided in barracks, which were often not formally categorized as dormitories and lacked basic bedding; settlements faced waste accumulation, wage payments were frequently delayed, food supplies were insufficient, and nutrition was poor. Additionally, workers were required to participate in unpaid Sunday community labor and subscribe to state loans. The austere conditions of everyday life were intended to be offset by ideological work conducted by party institutions, yet these measures often failed to address workers’ needs in the postwar years. Leisure opportunities were very limited, with cultural centers present only in towns and larger settlements.Both oblasts displayed similar power strategies directed by central authorities and faced common professional and domestic challenges. However, the tactics adopted to solve these problems frequently differed, shaped by the political, territorial, and cultural specifics of each region.
Keywords: Tuva; Tuvan Autonomous Oblast; Molotov Oblast; forestry; timber enterprise; everyday life; migration; wages; nutrition norms